PENGEMBANGAN MODEL MANAJEMEN PELATIHAN METODE MATHERNAL REPLEKTIF BERBASIS SENSITIVITAS HUMANIS DALAM PENINGKATAN KINERJA GURU SLB TUNARUNGU DI KABUPATEN DELI SERDANG - Purba, Cawir Rufunus; Siman, Siman; Pangaribuan, Wanapri; Simare-Mare, Aman; Purba, Sukarman; Purba, Saut (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2024)
The study aims to analyse: (1) a viable management model for training reflective maternal methods based on human sensitivity; and (2) an effective management model for training reflective maternal methods based on human sensitivity. The research was conducted using a Research and Development method with an ADDIE approach. The sample comprised 30 teachers from special schools for the hearing impaired, originating from 5 such schools in Deli Serdang Regency. The results concluded: (1) the reflective maternal training model based on human sensitivity is suitable for enhancing the performance of teachers in special schools for the hearing impaired in Deli Serdang Regency, with ratings from media experts, design experts, and language experts exceeding 90% in the very good category; and (2) the reflective maternal training model based on human sensitivity is effective in improving the performance of teachers in special schools for the hearing impaired in Deli Serdang Regency, with an N-Gain Score of g = 0.7284 > 0.7 and a percentage of 72.84%. Moreover, the research findings indicated improvements in the following aspects: lesson planning by 70.00%; lesson implementation by 63.33%; and evaluation of learning outcomes by 70.00%. The research results are expected to provide recommendations to the Provincial Education Office of North Sumatra, the Deli Serdang Regency Government, heads of special schools, and teachers of children with special needs to help students become independent and educated individuals.